(untitled) (Applied Biological Research, 2016)
The synergetic effect of Rhizobium sp. (Cajanus) and Piriformospora indica on bioenhancing activity, symbiotic parameters and grain yield of pigeon pea was evaluated. Nine genotypes were raised during kharif, 2013 at the Experimental Farm, HAU, Hisar (India). Rhizobium sp. and P. indica, alone or co-inoculated, along with untreated control were assessed for response of genotypes to these organisms on various metric traits. Significant differences among the genotypes for the studied traits indicated beneficial effect of both the organisms. Among the treatments, P. indica inoculation alone was most effective for most of the characters followed by dual inoculation of P. indica and Rhizobium. But for symbiotic traits the performance of Rhizobium alone was better than dual inoculation or P. indica alone. The genotypes Manak, Paras, UPAS 120, Pusa 991 and AH09-47 performed better with respect to symbiotic, growth and yield parameters. Hence, these genotypes could be used as parents in hybridization programme for genetic improvement of pigeon pea